2018
DOI: 10.3855/jidc.9908
|View full text |Cite
|
Sign up to set email alerts
|

Nasal colonization by methicillin-sensitive and methicillin-resistant Staphylococcus aureus among medical students

Abstract: Introduction: Nasal carriers of methicillin-resistant Staphylococcus aureus (MRSA) are common and play an important role in nosocomial infections. The prevalence rate and characterization of nasal carriers of MRSA among medical students in Jordan has not been investigated before. Methodology: The resistance of S. aureus to several antibiotics was tested using disc diffusion method, automatic Vitek 2, and penicillin binding protein (PBP) 2 slide test. Bacterial species and resistance genes were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 44 publications
4
20
1
Order By: Relevance
“…19 Research in Jordan in 2018 identified significant correlations between students with chronic disease and male gender with S. aureus carriage. 11 In Taiwan, Chen et al found correlations between hospital stay in the previous 1-year, antibiotic use and male gender with S. aureus carriage. 20 A 2017 study from China identified correlations with increased age and male gender and a significant difference with regular nasal cleaning.…”
Section: Resultsmentioning
confidence: 99%
“…19 Research in Jordan in 2018 identified significant correlations between students with chronic disease and male gender with S. aureus carriage. 11 In Taiwan, Chen et al found correlations between hospital stay in the previous 1-year, antibiotic use and male gender with S. aureus carriage. 20 A 2017 study from China identified correlations with increased age and male gender and a significant difference with regular nasal cleaning.…”
Section: Resultsmentioning
confidence: 99%
“…All participants consented to nasal swab collection and were invited to complete a questionnaire designed to comprehensively review the demographic information for every participant. The demographic data of both populations are illustrated in Tables 1 and 2 and in our previous publication [ 15 ] .…”
Section: Methodsmentioning
confidence: 99%
“…The collection of nasal swabs was carried out as described before [ 15 ] . Briefly, samples were collected under aseptic conditions, and the same swab was used for both nostrils.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations